2019
DOI: 10.5935/abc.20190125
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2, NF-κB and PPARβ/δ mRNA Expression Profile in Patients with Coronary Artery Disease

Abstract: Background: Oxidative stress and inflammation are present in coronary artery disease (CAD) and are linked to the activation of the transcription nuclear factor kappa B (NF-κB). To attenuate these complications, transcription factors like nuclear factor erythroid 2-related factor 2 (Nrf2) and peroxisome proliferator-activated receptor-β/δ (PPARβ/δ) can be activated to inhibit NF-κB. However, the available data on expression of NF-κB, Nrf2 and PPARβ/δ in CAD patients are limited.Objective: To evaluate the expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…NRF2 target genes HO-1 and GCLC were also decreased. However, this was not replicated by more recent work, which found no change in NRF2 expression in PBMCs derived from CAD patients [ 34 ], though the authors speculate that comorbid DM and antioxidant medication use in their patient cohort may have confounded their results.…”
Section: Nrf2 Expression and Function Is Changed In Several Diseasmentioning
confidence: 61%
“…NRF2 target genes HO-1 and GCLC were also decreased. However, this was not replicated by more recent work, which found no change in NRF2 expression in PBMCs derived from CAD patients [ 34 ], though the authors speculate that comorbid DM and antioxidant medication use in their patient cohort may have confounded their results.…”
Section: Nrf2 Expression and Function Is Changed In Several Diseasmentioning
confidence: 61%
“…A per-protocol analysis was performed according to other research articles already published by our group (Cardozo et al, 2016;Stockler-Pinto et al, 2012;Stockler-Pinto et al, 2010;Stockler-Pinto et al, 2014;Stockler-Pinto et al, 2015). Power calculations performed with our previous results (Barbosa et al, 2019) whose Nrf2 expression in individuals with CAD had an average of 1.35 and a standard deviation of 0.57 showed that 20 patients per group would have 80% test power to find a difference concerning the expression of Nrf2. Kolmogorov-Smirnov tests analysed the distribution for each treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The first study evaluated the pathophysiology of oxidative stress in atherosclerosis and showed a significantly lower Nrf2/ARE gene expression and cellular glutathione levels in CAD patients compared to those in healthy individuals (Mozzini et al, 2014). In the second and most recent study, patients with CAD were compared to patients with hypertension, dyslipidaemia and type 2 diabetes without CAD, and no differences were found in Nrf2, NF-κB, and NQO1 mRNA expression (Barbosa et al, 2019). In a recent review, Satta et al, (2017) reported that targeted activation of Nrf2 might help reduce CVD's impact.…”
Section: Discussionmentioning
confidence: 99%
“…e NF-kappa B signalling pathway is activated when the organism is stimulated or when reactive oxygen species become unbalanced, thus leading to the release of proinflammatory factors, such as IL-6, IL-8, TNF-α, iNOS, ICAM-1, VCAM-1, and cyclooxygenase (COX) 2. At the same time, increased production and release of proinflammatory factors further activate NF-kappa B, which in turn induces NODlike receptor protein-3 inflammasomes, leading to continuous amplification of initial inflammatory signals and the inflammatory cascade effect [9,10]. NF-kappa B also plays a central role in the activation of chemotactic cytokines, which contribute to the recruitment of monocytes/macrophages.…”
Section: Discussionmentioning
confidence: 99%